ANALISIS MOTIVASI SISWA MENGIKUTI PENGEMBANGAN DIRI SENI TARI DI SD NEGERI 20 LUBUK ALUNG KECAMATAN AMPEK NAGARI KABUPATEN AGAM - Fatimah; Farida Mayar; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This article aimed to explaining student's motivation infollowing dancing activities as their self-development activities in SD Negeri 20 Lubuk Alung Kecamatan Ampek Nagari Kabupaten Agam. The type of this research was descriptive qualitative research. The data ware collected from observation, interviews, and literature review. The data were analyzed byusing the phenomenology. The findings indicated that the students weremotivated enoughi following the dancing activiti as their self-development activities. It was seen from students enthuseiastic and earnest responseabout theactivities. Most student sexpressed their excitementand willingness tofollowthe activities.It could be councluded that the students following the dancing activities were those who cared for the dance art itself.